Productivity and efficiency of farmers growing four popular wheat varieties in Punjab, Pakistan - Battese, George E.; Nazli, Hina; Smale, Melinda (International Food Policy Research Institute, 2014)
HarvestPlus seeks to select one or more wheat varieties in Pakistan to biofortify with zinc to improve the health of the Pakistani population, especially women and children. The choice of varieties to enrich, and their diffusion patterns, will influence the productivity and efficiency of wheat production. This analysis seeks to (1) compare the relative productivity and efficiency of farmers currently growing the most widely diffused wheat varieties, and (2) update our understanding of factors that influence productivity and efficiency of wheat production. We estimate a stochastic production function model with data from a survey of wheat farmers conducted in Punjab, Pakistan, in 2011. We find no differences in technical inefficiency effects associated with farmers growing the top four varieties, either alone or in combination with other varieties. With respect to human capital, older farmers tend to be more technically inefficient than younger farmers, but education has no statistical significance. Wheat farmers with access to extension advice are more efficient. Smaller-scale farmers and those in the mixed production zone tend to be more technically inefficient. Later adopters were not less efficient than earlier adopters, but time to varietal change is negatively related to the efficiency of wheat production. Farmers growing wheat in the rice-wheat and cotton-wheat zones tend to be less productive (but more efficient) than farmers from the mixed zone. Finally, farmers whose land suffered from severe salinity or severe toxicity are less productive and efficient than other farmers.